Petrological, mineralogical and geochemical studies of Zhongchang and Yantiangou ultramafic intrusions from the Panxi region, Sichuan Province, S-W China. Metallogenic and Exploration implications - Malatji, Tsholofelo S (Rhodes University, Faculty of Science, Department of Geology, 2014)
The Emeishan Large Igneous Province is one of the largest igneous provinces in the world. It is marked by basaltic extrusives that vary in Ti amount, classified as high Ti and low Ti. Several mafic to ultramafic intrusions occur in the province as well as granitic intrusions. The mafic-ultramafic intrusions are associated with mineralization; large layered utlramafic intrusions bearing Fe-Ti-V mineralization, while small dyke like or sill like intrusions contain Cu-Ni-PGE mineralization. The Zhongchang and Yantiangou mafic- ultramafic intrusions are small such intrusions bearing Ni-Cu-PGE mineralization. The deposits show a lot of similarities in source magma, evolution and mineralization. Parental magma for both deposits show alkaline tendencies, and a high Mg # indicative of primitive magma that underwent little crustal contamination. Mantle range Cu/Pd ratios show parental magma fertile in chalcophile elements and both deposits proceed to show depleted mantle normalized values as a result of sulphide saturation and subsequent mineralization. Mineralization in Zhongchang is hosted at the contact between peridotite and pyroxenite, interstitial to olivine and clinopyroxene. Alteration minerals include epidote and chlorite. High Cu/Pd ratios suggest earlier sulphide saturation and removal of a PGE sulphide, and a second sulphide saturation phase resulted in Ni-Cu mineralization. Mineralization in Yantiangou is hosted in biotite effectively following fractionation of olivine and clinopyroxene after which sulphide saturation occurred, precipitating sulphide minerals in biotite. Pyrite and millerite occur as a result of late stage hydrothermal alteration. Cu/Pd ratios are high indicating prior sulphide saturation occurred where PGE partitioned into sulphides. Ni/MgO ratios observed for both deposits indicate a state of sulphide under saturation where PGE partitioned into tellurides and bismurthinides and Ni into olivine. Average tenors for mineralized units are; Zhongchang at 5%Ni, 9% Cu, 4300ppb Pt and 2000ppb Pd, and Yantiangou having relatively lower tenors at 3.2%Ni, 6.5% Cu, 3000ppb Pt and 1300 ppb Pd.
Keywords: Mineralogy -- China; Geochemistry -- China